If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8 = -40 + -2 Reorder the terms: 8 + 6x = -40 + -2 Combine like terms: -40 + -2 = -42 8 + 6x = -42 Solving 8 + 6x = -42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 6x = -42 + -8 Combine like terms: 8 + -8 = 0 0 + 6x = -42 + -8 6x = -42 + -8 Combine like terms: -42 + -8 = -50 6x = -50 Divide each side by '6'. x = -8.333333333 Simplifying x = -8.333333333
| (-a)-b=(-b)-a | | 7=z+9 | | 9z+1=46 | | 2ln(3-x)=1 | | -a-b=-b-a | | 11x+7x+90=x+x | | b+2a+c= | | x-2/3-x+1/4=x | | 8w-1=31 | | -3(x-1)=x-5 | | x+75=x+115 | | 7(n-5)-(8n-1)=-2n | | -6x+y=16 | | 10+10t-5t^2=0 | | 6b+10=46 | | 4(x+8)=-60 | | 18x+90=2x | | 0.5(x+4)=197 | | x+88=108+x | | 4x+60+x=180 | | 14x^2+70x+25=48 | | 2w+100=4w | | 3a+2b=5ab | | 6(c-9)=-24 | | 2[7-7(1-x)]+4x=-16+3[6(x+1)-3x] | | 7f=42 | | -x+4-2x=-(2+x) | | x+4+x+2+x+5=360 | | 7a+3b+6c= | | 8(3y-4)= | | -x+4-2x=-(2x+2) | | (4w-6)(1-w)=0 |